Zoledronic acid for the treatment of pregnancy-associated femoral head necrosis: A case report - Estella Musacchio; Leonardo Sartori (Elsevier, 2020)
Introduction: The management of pregnancy-associated femoral necrosis is controversial. Conservative management may eventually lead to hip replacement. Case: A 40-year-old woman developed necrosis of the left hip during her first pregnancy. Treatment with zoledronic acid three months after delivery resulted in rapid reduction of the necrotic area. The patient's second pregnancy shortly afterwards had no complications. A magnetic resonance scan three years later documented complete resolution. Conclusion: Femoral head necrosis should be suspected in the differential diagnosis of pain in pregnancy. Zoledronic acid given in the early stages prevented progression to hip arthritis in this case. Keywords: Avascular necrosis, Femoral head, Osteonecrosis, Pregnancy, Zoledronic acid